Wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles and preparation method of wood carbon aerogel electromagnetic shielding material

By loading magnetic iron-cobalt nanoparticles in wooden carbon aerogels, the problems of complex interface regulation, insufficient pores and high manufacturing costs of traditional carbon-based magnetic composite materials are solved, and efficient electromagnetic wave shielding and electric heat conversion performance are achieved.

CN119653752APending Publication Date: 2025-03-18SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411809354.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing carbon-based magnetic composite materials have challenges in interface structure design and magnetic dielectric components regulation, resulting in complex interface regulation, insufficient pores and high manufacturing costs.

Method used

By loading magnetic iron-cobalt nanoparticles into wood-carbon aerogels with multi-level directional channel structures, using natural wood as carbon source, ultra-light wood-carbon aerogels are constructed through delignification and high-temperature carbonization treatment, and self-assembling the reaction-loaded magnetic iron-cobalt nanoparticles in situ inside it.

Benefits of technology

The uniform dispersion of magnetic metal nanoparticles in directional porous wood carbon-based materials is achieved, the propagation path and loss mechanism of electromagnetic waves are optimized, and the electromagnetic wave shielding performance and electric heat conversion performance are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653752A_ABST
    Figure CN119653752A_ABST
Patent Text Reader

Abstract

The invention discloses a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles and a preparation method of the wood carbon aerogel electromagnetic shielding material. The electromagnetic shielding material is of a multi-stage directional pore channel structure, and meanwhile, the magnetic iron-cobalt nanoparticles are uniformly distributed on the inner wall of a pore channel; the surface of the electromagnetic shielding material is rough, more heterogeneous interfaces can be generated, and dielectric loss of electromagnetic waves is facilitated. The multi-stage directional pore channel structure has excellent conductivity, dielectric property and magnetic property, so that the composite material can optimize the propagation path of electromagnetic waves and shows various electromagnetic wave loss mechanisms. The invention aims to realize uniform dispersion and loading of the magnetic metal nanoparticles in the oriented porous wood carbon-based material, so that the problems of complex interface regulation, insufficient pores, high manufacturing cost and the like of the traditional carbon-based magnetic composite material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic wave shielding materials, and specifically relates to a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles and a preparation method thereof. Background Art

[0002] The widespread use of wireless communications and the rapid development of smart electronic devices have brought great convenience to human life. At the same time, electromagnetic pollution has also had adverse effects on equipment, human body and surrounding environment. Therefore, the development of efficient, thin, cheap and safe electromagnetic shielding materials is crucial to ensure the stable operation of electronic equipment and human health. Carbon materials and metal materials are two common electromagnetic shielding materials.

[0003] Compared with single components, the construction of composite electromagnetic shielding materials by combining carbon-based materials and magnetic metals is conducive to the synergistic use of the advantages of the two materials and the realization of multiple electromagnetic loss mechanisms. However, common carbon materials such as graphene and carbon nanotubes are usually expensive, have complex preparation processes, and are made from fossil energy, which does not meet the requirements of green and sustainable development.

[0004] At the same time, the interface structure design, pore structure, magnetic metal particle size and dispersion of magnetic metal and carbon-based composites have an important influence on the electromagnetic wave loss mechanism and shielding performance. However, reasonable structural design and regulation of magnetic dielectric components still face challenges. Summary of the invention

[0005] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles and a preparation method thereof. Natural wood with a directional multi-level pore structure is used as raw material, an ultra-light wood aerogel is constructed by delignification, and a metal organic complex is loaded in the internal pores of the wood aerogel through an in-situ self-assembly reaction, aiming to achieve uniform dispersion and loading of magnetic metal nanoparticles in the directional porous wood carbon-based material, thereby solving the problems of complex interface regulation, insufficient porosity, and high manufacturing cost of traditional carbon-based magnetic composite materials.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles, the electromagnetic shielding material presents a multi-level directional pore structure, and magnetic iron-cobalt nanoparticles are evenly distributed on the inner wall of the pore; the electromagnetic shielding material has a rough surface and can produce more heterogeneous interfaces, which is beneficial to the dielectric loss of electromagnetic waves.

[0008] The multi-level directional pore structure has excellent conductivity, dielectric properties and magnetic properties, enabling the composite material to optimize the propagation path of electromagnetic waves and exhibit a variety of electromagnetic wave loss mechanisms.

[0009] A method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles comprises the following steps:

[0010] Step 1: Delignify the cut wood chips and then freeze-dry them to obtain delignified wood aerogel (WA);

[0011] Step 2: The obtained WA is subjected to coordination self-assembly reaction with iron cobalt salt and organic ligand in a reactor, followed by freeze drying to obtain a wood aerogel loaded with iron cobalt-adenine complex (FeCoA@WA);

[0012] Step 3: Carbonize FeCoA@WA at high temperature in an inert gas to obtain wood carbon aerogel loaded with magnetic iron-cobalt nanoparticles (FeCo NP @WCA) electromagnetic shielding materials.

[0013] In step 1, the wood chips are balsa wood chips, and the size of the wood chips is 3×0.5×4 cm 3 (radial × tangential × longitudinal), wood chip density is 0.08~0.12g / cm 3 .

[0014] In step 1, the specific preparation process of WA is as follows:

[0015] The balsa wood chips are immersed in a 2wt% NaClO2 aqueous solution, and the pH value is adjusted to 4-5 with glacial acetic acid. The reaction temperature of the mixed reaction liquid is 100-120°C, the reaction time is 10-16 hours, and WA is obtained by vacuum freeze drying.

[0016] In the step 2, the iron-cobalt salts are ferrous acetate and cobalt acetate tetrahydrate, the molar ratio of ferrous acetate to cobalt acetate tetrahydrate is 1:1, and the concentration is 5-10 mg / mL; the organic ligand is adenine, and the concentration is 2-5 mg / mL, and the iron-cobalt salt and adenine form iron-cobalt salt / adenine.

[0017] In step 2, the mass ratio of WA to iron-cobalt salt / adenine is 4: 1 to 3: 1. The coordination of adenine and metal salt can effectively inhibit the aggregation of metal ions, facilitate the dispersion of iron-cobalt ions, and achieve uniform distribution of magnetic metal iron-cobalt nanoparticles.

[0018] In the step 2, the solvent thermal self-assembly reaction temperature is 130-160° C., and the reaction time is 3-6 hours. Such reaction conditions are conducive to the in-situ synthesis of the iron-cobalt-adenine complex in the WA porous network.

[0019] In step 3, the inert gas is argon, the carbonization temperature is 900-1000°C, the heating rate is 5°C / min-10°C / min, and the carbonization time is 2-4 hours. Under this carbonization condition, WA is converted into a conductive carbon aerogel network, and the iron-cobalt-adenine complex loaded in the carbon aerogel is converted into iron-cobalt nanoparticles, and N doping is achieved on the carbonaceous substrate.

[0020] The wood carbon aerogel material loaded with magnetic iron-cobalt nanoparticles is applied in the field of electromagnetic shielding materials.

[0021] Beneficial effects of the present invention:

[0022] The carbon source selected by the present invention is natural wood, which has the characteristics of good biocompatibility, light weight, good processability, etc. Its inherent multi-level directional channels and rich surface functional groups provide an ideal carrier for the in-situ assembly of metal-organic complexes. After high-temperature carbonization treatment, the wood carbon aerogel is endowed with excellent conductivity, which is beneficial to the reflection loss of electromagnetic waves; the multi-level channels of wood not only create conditions for the uniform dispersion of magnetic metal nanoparticles and realize the magnetic loss of electromagnetic waves, but also its honeycomb porous structure also helps to optimize the propagation path of electromagnetic waves and realize multiple reflections of electromagnetic waves inside the carbon aerogel composite material.

[0023] Based on this, the wood carbon aerogel material loaded with magnetic iron-cobalt nanoparticles showed excellent electromagnetic wave shielding performance, with the highest electromagnetic shielding efficiency reaching 66.2dB.

[0024] In addition, the wood carbon aerogel material loaded with magnetic iron-cobalt nanoparticles also shows excellent electrothermal conversion performance. When the external voltage is 5V, the surface temperature can reach 78°C and can be used as a heating source. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 WA and FeCo prepared in Example 1 of the present invention NP @WCA Digital photo of electromagnetic shielding materials.

[0026] Figure 2 It is FeCo in Example 1 of the present invention. NP @SEM photo of WCA electromagnetic shielding material.

[0027] Figure 3 It is FeCo in Example 1 of the present invention. NP @WCA Transmission electron microscope (TEM) photo of electromagnetic shielding material.

[0028] Figure 4 It is the X-ray diffraction (XRD) spectrum of the electromagnetic shielding material prepared in Example 1 and Comparative Examples 1-3 of the present invention.

[0029] Figure 5 The FeCo prepared in Example 1 of the present invention NP @WCA hysteresis loop diagram of electromagnetic shielding material.

[0030] Figure 6 It is the electrical conductivity of the electromagnetic shielding materials prepared in Example 1 of the present invention and Comparative Examples 1-3.

[0031] Figure 7 It is a graph of the electromagnetic shielding efficiency of the electromagnetic shielding materials prepared in Example 1 of the present invention and Comparative Examples 1-3 at 8.2-12.4 GHz.

[0032] Figure 8 The FeCo prepared in Example 1 of the present invention NP @WCA Temperature variation curve of electromagnetic shielding material under different DC voltages. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0034] Embodiment 1:

[0035] This embodiment provides a method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles, which is prepared by the following steps:

[0036] Step 1: Take 18g NaClO2 and dissolve it in 900mL water, add 12mL glacial acetic acid to adjust the pH value of the NaClO2 solution to 4.5, add 5g balsa wood chips to the above solution, and heat the reaction solution at 110°C for 12 hours to remove most of the lignin; then, the delignified wood chips are soaked and washed with deionized water, and vacuum freeze-dried to obtain delignified wood aerogel (WA).

[0037] Step 2: Weigh 0.26g of ferrous acetate, 0.37g of cobalt acetate tetrahydrate and 0.27g of adenine, add them to 100mL of DMF solution, heat and stir on a magnetic stirrer until the iron cobalt salt and adenine are completely dissolved, and transfer this solution and WA in step 1 to a high-pressure reactor and react at 150°C for 5 hours. After the reaction product is repeatedly soaked and washed with deionized water, it is vacuum freeze-dried to obtain a wood aerogel (FeCoA@WA) loaded with an iron cobalt-adenine complex.

[0038] Step 3: The FeCoA@WA obtained in step 2 was placed in an alumina crucible, and argon was introduced into a tube furnace, and heated to 1000°C at a heating rate of 5°C / min and kept warm for 2 hours to finally obtain a wood carbon aerogel loaded with magnetic iron-cobalt nanoparticles (FeCo NP @WCA) electromagnetic shielding materials.

[0039] Embodiment 2:

[0040] This embodiment provides a method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles, which is prepared by the following steps:

[0041] Step 1: The basic operation of preparing WA in step 1 of this embodiment is basically the same as step 1 of embodiment 1, and will not be repeated here.

[0042] Step 2: Weigh 0.17g of ferrous acetate, 0.25g of cobalt acetate tetrahydrate and 0.27g of adenine, add them to 100mL of DMF solution, heat and stir on a magnetic stirrer until the iron cobalt salt and adenine are completely dissolved, and transfer this solution and WA in step 1 to a high-pressure reactor and react at 150°C for 5 hours. After the reaction product is repeatedly soaked and washed with deionized water, it is vacuum freeze-dried to obtain a wood aerogel (FeCoA@WA) loaded with an iron cobalt-adenine complex.

[0043] Step 3: The FeCoA@WA obtained in step 2 was placed in an alumina crucible, and argon was introduced into a tube furnace, and heated to 1000°C at a heating rate of 5°C / min and kept warm for 2 hours to finally obtain a wood carbon aerogel loaded with magnetic iron-cobalt nanoparticles (FeCo NP @WCA) electromagnetic shielding materials.

[0044] Embodiment 3:

[0045] This embodiment provides a method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles, which is prepared by the following steps:

[0046] Step 1: The basic operation of preparing WA in step 1 of this embodiment is basically the same as step 1 of embodiment 1, and will not be repeated here.

[0047] Step 2: Weigh 0.35g of ferrous acetate, 0.50g of cobalt acetate tetrahydrate and 0.27g of adenine, add them to 100mL of DMF solution, heat and stir on a magnetic stirrer until the iron cobalt salt and adenine are completely dissolved, and transfer this solution and WA in step 1 to a high-pressure reactor and react at 150°C for 5 hours. After the reaction product is repeatedly soaked and washed with deionized water, it is vacuum freeze-dried to obtain a wood aerogel (FeCoA@WA) loaded with an iron cobalt-adenine complex.

[0048] Step 3: The FeCoA@WA obtained in step 2 was placed in an alumina crucible, and argon was introduced into a tube furnace, and heated to 1000°C at a heating rate of 5°C / min and kept warm for 2 hours to finally obtain a wood carbon aerogel loaded with magnetic iron-cobalt nanoparticles (FeCo NP @WCA) electromagnetic shielding materials.

[0049] Embodiment 4:

[0050] This embodiment provides a method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles, which is prepared by the following steps:

[0051] Step 1: The basic operation of preparing WA in step 1 of this embodiment is basically the same as step 1 of embodiment 1, and will not be repeated here.

[0052] Step 2: Weigh 0.26g of ferrous acetate, 0.37g of cobalt acetate tetrahydrate and 0.27g of adenine, add them to 100mL of DMF solution, heat and stir on a magnetic stirrer until the iron cobalt salt and adenine are completely dissolved, and transfer this solution and WA in step 1 to a high-pressure reactor and react at 150°C for 5 hours. After the reaction product is repeatedly soaked and washed with deionized water, it is vacuum freeze-dried to obtain a wood aerogel (FeCoA@WA) loaded with an iron cobalt-adenine complex.

[0053] Step 3: The FeCoA@WA obtained in step 2 was placed in an alumina crucible, and argon was introduced into a tube furnace, and heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to finally obtain a wood carbon aerogel loaded with magnetic iron-cobalt nanoparticles (FeCo NP @WCA) electromagnetic shielding materials.

[0054] Comparative Example 1:

[0055] This comparative example provides a method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron nanoparticles, which is prepared by the following steps:

[0056] Step 1: The basic operation of preparing WA in step 1 of this comparative example is basically the same as step 1 of embodiment 1, and will not be repeated here.

[0057] Step 2: Weigh 0.52g of ferrous acetate and 0.27g of adenine, add them to 100mL of DMF solution, heat and stir on a magnetic stirrer until the iron salt and adenine are completely dissolved, and transfer this solution and the WA in step 1 to a high-pressure reactor and react at 150°C for 5 hours. After the reaction product is repeatedly soaked and washed with deionized water, it is vacuum freeze-dried to obtain a wood aerogel (FeA@WA) loaded with an iron-adenine complex.

[0058] Step 3: The FeA@WA obtained in step 2 was placed in an alumina crucible, and argon was introduced into a tube furnace, and heated to 1000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to finally obtain a wood carbon aerogel loaded with magnetic iron nanoparticles (Fe NP @WCA) electromagnetic shielding materials.

[0059] Comparative Example 2:

[0060] This comparative example provides a method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic cobalt nanoparticles, which is prepared by the following steps:

[0061] Step 1: The basic operation of preparing WA in step 1 of this comparative example is basically the same as the process of step 1 of embodiment 1, and will not be repeated here.

[0062] Step 2: Weigh 0.75 g of cobalt acetate tetrahydrate and 0.27 g of adenine, add them to 100 mL of DMF solution, heat and stir on a magnetic stirrer until the cobalt salt and adenine are completely dissolved, and transfer this solution and the WA in step 1 to a high-pressure reactor and react at 150°C for 5 hours. After the reaction product is repeatedly soaked and washed with deionized water, it is vacuum freeze-dried to obtain a wood aerogel (CoA@WA) loaded with a cobalt-adenine complex.

[0063] Step 3: The Co@WA obtained in step 2 was placed in an alumina crucible, and argon was introduced into a tube furnace, and heated to 1000°C at a heating rate of 5°C / min and kept warm for 2 hours to finally obtain a wood carbon aerogel loaded with magnetic cobalt nanoparticles (Co NP @WCA) electromagnetic shielding materials.

[0064] Comparative Example 3:

[0065] This comparative example provides a method for preparing a metal-free wood carbon aerogel electromagnetic shielding material. Compared with the method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles described in Example 1, the difference is that as a control example, no iron-cobalt-adenine complex and iron-cobalt nanoparticles are introduced, and only delignified wood aerogel (WA) is used as a carbonization precursor, and the aerogel is prepared by the following steps:

[0066] Step 1: The basic operation of preparing WA in step 1 of this comparative example is basically the same as the process of step 1 of embodiment 1, and will not be repeated here.

[0067] Step 2: The WA obtained in step 1 is placed in an alumina crucible, and argon gas is introduced into a tubular furnace, and heated to 1000°C at a heating rate of 5°C / min, and kept warm for 2 hours to finally obtain a wood carbon aerogel (WCA) electromagnetic shielding material.

[0068] Test Example 1:

[0069] Take WA and FeCo prepared in Example 1 NP @WCA electromagnetic shielding material, take photos with digital camera respectively, the images are as follows Figure 1It can be clearly seen that the volume of the carbonized composite material becomes smaller, the surface becomes a little rough, and more heterogeneous interfaces can be produced, which is beneficial to the dielectric loss of electromagnetic waves.

[0070] Take the FeCo prepared in Example 1 NP @WCA electromagnetic shielding materials were tested by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the images obtained were as follows: Figure 2 and 3 shown.

[0071] Depend on Figure 2 It can be observed that the electromagnetic shielding material retains the multi-level directional pore structure of natural wood in the microstructure, and the inner wall of the pores is evenly dispersed with magnetic nanoparticles. A large number of pore wall structures can enhance the multiple reflections / scattering of electromagnetic waves, hinder the propagation path of electromagnetic waves, and effectively promote the attenuation of electromagnetic waves.

[0072] Figure 3 It was further observed that the particle size of the magnetic nanoparticles was about 200 nanometers, and there was no obvious agglomeration. The composite of magnetic particles and carbonized wood can improve the graphitization degree of the composite material, thereby improving its conductivity.

[0073] Figure 4 The X-ray diffraction (XRD) patterns of the electromagnetic shielding materials prepared in Example 1 and Comparative Examples 1-3 are given. NP The diffraction peaks of @WCA sample at 45.1° and 65.2° correspond to the (110) and (200) crystal planes of metal Fe, respectively. NP The peaks of @WCA sample at 44.2°, 51.6° and 75.8° correspond to the (111), (200) and (210) crystal planes of metal Co, respectively. NP The WCA sample showed diffraction peaks of both metallic Fe and Co in the XRD spectrum, confirming the presence of magnetic FeCo nanoparticles.

[0074] Figure 5 The FeCo prepared in Example 1 is given NP @WCA hysteresis loop of electromagnetic shielding material. The electromagnetic shielding material shows ferromagnetism. The source of magnetism is due to the introduction of metal Fe and Co nanoparticles.

[0075] Figure 6 The electrical conductivity of the electromagnetic shielding materials prepared in Example 1 and Comparative Examples 1 to 3 is given. Due to the inherent high electrical conductivity of metal materials, the electrical conductivity of the electromagnetic shielding material with the addition of magnetic nanoparticles is also significantly improved.

[0076] Figure 7The electromagnetic shielding efficiency diagram of the electromagnetic shielding materials prepared in Example 1 and Comparative Examples 1-3 at 8.2-12.4 GHz is given. Compared with electromagnetic shielding materials with a single magnetic metal or without a magnetic metal, the WCA electromagnetic shielding material rich in magnetic FeCo nanoparticles has a better electromagnetic wave shielding performance, and the highest electromagnetic shielding efficiency reaches 66.2dB. This is mainly because the introduction of magnetic nanomaterials enhances the magnetic loss of the composite material, and the directional porous structure inside the wood carbon aerogel can achieve multiple reflections of electromagnetic waves and optimize the electromagnetic wave propagation path.

[0077] Figure 8 The FeCo prepared in Example 1 is given NP @WCA Temperature variation curve of electromagnetic shielding material under different DC voltages (1V-5V). Due to its good conductivity, FeCo NP @Under a voltage of 5V, the surface temperature of the WCA composite material can quickly rise to 78°C, showing good electrothermal conversion performance.

Claims

1. A wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles, wherein the electromagnetic shielding material presents a multi-level directional pore structure, and magnetic iron-cobalt nanoparticles are evenly distributed on the inner wall of the pore; the electromagnetic shielding material has a rough surface, which can produce more heterogeneous interfaces, which is beneficial to the dielectric loss of electromagnetic waves.

2. The method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles according to claim 1, characterized in that: The following steps are involved: Step 1: Delignify the cut wood chips and then freeze-dry them to obtain delignified wood aerogel (WA); Step 2: The obtained WA is subjected to coordination self-assembly reaction with iron cobalt salt and organic ligand in a reactor, followed by freeze drying to obtain a wood aerogel loaded with iron cobalt-adenine complex (FeCoA@WA); Step 3: Carbonize FeCoA@WA at high temperature in an inert gas to obtain wood carbon aerogel loaded with magnetic iron-cobalt nanoparticles (FeCo NP @WCA) electromagnetic shielding materials.

3. The method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles according to claim 2, characterized in that: In step 1, the wood chips are balsa wood chips, and the size of the wood chips is 3×0.5×4 cm 3 (radial × tangential × longitudinal), wood chip density is 0.08~0.12g / cm 3 .

4. The method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles according to claim 2, characterized in that: In step 1, the specific preparation process of WA is as follows: The balsa wood chips are immersed in a 2wt% NaClO2 aqueous solution, and the pH value is adjusted to 4-5 with glacial acetic acid. The reaction temperature of the mixed reaction liquid is 100-120°C, the reaction time is 10-16 hours, and WA is obtained by vacuum freeze drying.

5. The method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles according to claim 2, characterized in that: In the step 2, the iron-cobalt salts are ferrous acetate and cobalt acetate tetrahydrate, the molar ratio of ferrous acetate to cobalt acetate tetrahydrate is 1:1, and the concentration is 5-10 mg / mL; the organic ligand is adenine, and the concentration is 2-5 mg / mL, and the iron-cobalt salt and adenine form iron-cobalt salt / adenine.

6. The method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles according to claim 5, characterized in that: In the step 2, the mass ratio of WA to iron cobalt salt / adenine is 4:1 to 3:

1.

7. The method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles according to claim 2, characterized in that: In the step 2, the solvent thermal self-assembly reaction temperature is 130-160° C., and the reaction time is 3-6 hours.

8. The method for preparing a wood carbon aerogel electromagnetic shielding material loaded with magnetic iron-cobalt nanoparticles according to claim 2, characterized in that: In step 3, the inert gas is argon, the carbonization temperature is 900-1000° C., the heating rate is 5° C. / min-10° C. / min, and the carbonization time is 2-4 hours.

9. The use of the wood-carbon aerogel material loaded with magnetic iron-cobalt nanoparticles according to any one of claims 1 to 8, characterized in that: Wood carbon aerogel materials loaded with magnetic iron-cobalt nanoparticles are used in the field of electromagnetic shielding materials.